RISK DISCLOSURES IN THE MOST ADMIRED COMPANY’S REPUTATION - Juniati Gunawan; Criselda Elsa (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study aims to examine the influence of risk disclosures on a company's reputation, which was measured by the Indonesia’s Most Admired Company (IMAC) nomination in 2018. The sample applies the whole population registered in the IMAC. There were 133 companies which provided all data required. Using content analysis to calculate risk disclosures as independent variable and company's reputation by the Corporate Image Index (CII) as dependent variable, this study shows that risk disclosures has a significant influence on the company's reputation.The results provide a new perspective on disclosure risk and company’s reputation since previous studies were very limited searching on risk disclosures related to corporate image. Since CII is publicly available, the risk disclosures need to be paid attention to balance the information for the stakeholders. Hence, this study contributes greatly for both academic and practice to understand that risk information may impact the corporate reputation, and therefore, adequate and balance disclosure (negative and positive information) is required.